2017
DOI: 10.1177/0954410017745901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tip clearance size on the unsteady flow behaviors and performance in a counter-rotating axial flow compressor

Abstract: This paper presents the studies performed to better understand the effects of increased tip clearance size on the unsteady flow behaviors and overall performance under the rotor–rotor interaction environment in a counter-rotating axial flow compressor. The investigation method is based on the three-dimensional unsteady Reynolds-averaged Navier–Stokes simulations. The results show that the intensified tip leakage flow in front rotor (R1) caused by the increased tip clearance size will lead to the growth of inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Because the number of nodes required for LES simulation of stator-rotor configurations with tip clearance modelling is significantly high (up to several dozens of million cells), unsteady RANS (URANS) modelling is still being used by a number of researchers as a useful approach, with an acceptable compromise between accuracy and computational cost. Effectively, recent investigations have provided valuable information, showing that it is feasible to accurately simulate these three-dimensional, vortical structures using URANS modelling (Zhang et al, 2015;Jung and Joo, 2018;Mao et al, 2019). Moreover, when the fullunsteady sliding mesh technique is used in multistage environments, the URANS approach turns to be the more realistic and practicable option.…”
Section: Hff 3010mentioning
confidence: 99%
“…Because the number of nodes required for LES simulation of stator-rotor configurations with tip clearance modelling is significantly high (up to several dozens of million cells), unsteady RANS (URANS) modelling is still being used by a number of researchers as a useful approach, with an acceptable compromise between accuracy and computational cost. Effectively, recent investigations have provided valuable information, showing that it is feasible to accurately simulate these three-dimensional, vortical structures using URANS modelling (Zhang et al, 2015;Jung and Joo, 2018;Mao et al, 2019). Moreover, when the fullunsteady sliding mesh technique is used in multistage environments, the URANS approach turns to be the more realistic and practicable option.…”
Section: Hff 3010mentioning
confidence: 99%
“…Previous studies indicated that the capacity of MCRFs can be modified by optimizing the design of the impeller structures and the angles of installation. (10)(11)(12)(13)(14) Some studies (15)(16)(17)(18)(19) found that optimizing the gap between the impeller tips of rotors may significantly improve the efficiency and stability of operation for an MCRF system. This is because the gap size of R1 may affect the occurrence and development of a turbulence trail in the impeller tip region, and thus the flow conditions in the impellers of R2.…”
Section: Introductionmentioning
confidence: 99%
“…While improving the pathological characteristics of AD, can it improve the gamma rhythm that is closely related to cognitive function, and provide neuro-physiological mechanisms of cell function for aerobic exercise to improve the behavior of the AD model. 1…”
Section: Introductionmentioning
confidence: 99%